Bedtime for Baby Shark : doo doo doo doo doo doo - Bajet,John John (Newyork Cartwheel Books, an imprint of Scholastic Inc., 2019)
silly illustrated story of a shark family's bedtime routine ..."-- Publisher's description
Keywords: English Picture book